Endometrial expression of relaxin and relaxin receptor in endometriosis - Morelli, Sara S. (2010)
Our studies demonstrate significantly lower expression of relaxin and its receptor in ectopic endometriotic tissues than their expression in eutopic endometrium and in endometrium from normal controls. These data suggest that in normal and eutopic endometrium, relaxin may exert a protective effect against endometriosis.